(3QSGdI aj eSCdI GdcMds - (3YKeGf Hf YeQ Hf CHj HcQ Hf jhfS GdeGdcj GdcQOj GdCSfGFj GdeUQj , CHh YeQh LeGd GdOjf GHf GdMGLH , J (B646 (3g` s
(3ChdgG (B:s
(3hHYO, adeG GfJgJ eHGMKGJj eY CUMGHj GdPjf dge OQHI dJMbjb GdeYGfj GdYGUjI, hGdeHGfj GdbGUjI s
(3BNQgG (B:s
(3bhdg SGQjkG efUhH Hhbj, hbjd MGd ef VejQ CNha hbjd JejjR efg hGddg CYde HGdUhGH s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGfj hGdCNjQs
(3GdePchQI aj cGajI GHf GdMGLHs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B211 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B265s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B2 - (3U (B138 s
Keywords: (3GdfMhs